Electoral dynamics in the Philippines money politics, patronage and clientelism at the grassroots - Aspinall, Edward; Weiss, Meredith (National University of Singapore, 2019)
The role of clientism, political machines, and money in grassroots electioneering in the Philippines has been much analyzed by those who study the subject, but never as extensively as Allen Hicken, Edward Aspinall, and Meredith Weiss do in Electoral Dynamics in the Philippines. Combining in-depth ethnographic fieldwork in localities across the Philippines during the 2016 elections with polling data and national comparative data, this study sheds light on the organization of elections and electioneering across the Philippines. How do candidates choose to appeal to voters, and how do they get out the vote? How do voters respond to different kinds of appeals? How important are patronage and clientism? What are the networks within which patronage is delivered? What do the political machines look like in elections influenced by social media? The book identifies commonalities and differences across the Philippines while speaking to current debates in political science about elections in developing democracies, the structure and organization of clientelism, and the role of money in elections"--back cover.